Focal dermal hypoplasia (goltz–gorlin syndrome): A new case with a novel variant in the PORCN gene (c.1250T>C:p.F417S) and unusual spinal anomaly. Issue 7 (21st May 2013) - Garavelli, Livia; Simonte, Graziella; Rosato, Simonetta; Wischmeijer, Anita; Albertini, Enrico; Guareschi, Elisa; Longo, Caterina; Albertini, Giuseppe; Gelmini, Chiara; Greco, Chiara; Errico, Stefania; Savino, Gustavo; et al.
Abstract Focal dermal hypoplasia (FDH; Goltz–Gorlin syndrome; OMIM 305600) is a disorder that features involvement of the skin, skeletal system, and eyes. It is caused by loss‐of‐function mutations in the PORCN gene. We report a young girl with FDH, microphthalmos associated with colobomatous orbital cyst, dural ectasia and cystic malformation of the spinal cord, and a de novo variant in PORCN. This association has not been previously reported, and based on these observations the phenotypic spectrum of FDH might be broader than previously appreciated. It would be prudent to alter the suggested surveillance for this rare disorder. © 2013 Wiley Periodicals, Inc.